Factors Affecting Spitting Behavior on Betel Consumers in Applicating PHBS Public Places in Pasar Raya Simalungun Regency - Kartini S.H Panjaitan; Lita Sri Andayani; R. Kintoko Rochadi (Britain International for Academic Research (BIAR) Publisher, 2020)
This study discusses about factors affecting spitting behavior on betel consumers in applicating PHBS public places in Pasar Raya Simalungun Regency. This research is a descriptive study to describe factors affecting spitting behavior on betel consumers in applicating phbs public places. This research is conducted at Pasar Raya Simalungun Regency. The time for conducting the research starts from the beginning of November 2018 until completion. The result shows Respondents are more well-informed, namely 44 people (43%), more respondents with shelter availability of spit consuming betel, namely 55 people (63.2%). More respondents with poor health support, 68 people (78.2%).